Changes in phytophagous insect host ranges following the invasion of their community: Long‐term data for fruit flies - Charlery de la Masselière, Maud (Ecol Evol, 2017)
The invasion of an established community by new species can trigger changes in community structure. Invasions often occur in phytophagous insect communities, the dynamics of which are driven by the structure of the host assemblage and the presence of competitors. In this study, we investigated how a community established through successive invasions changed over time, taking the last invasion as the reference. The community included four generalist and four specialist species of Tephritidae fruit flies. We analyzed a long‐term database recording observed numbers of flies per fruit for each species on 36 host plants, over 18 years, from 1991 to 2009. Community structure before the last invasion by Bactrocera zonata in 2000 was described in relation to host plant phylogeny and resource availability. Changes in the host range of each species after the arrival of B. zonata were then documented by calculating diversity indices. The flies in the community occupied three types of niches defined on the basis of plant phylogeny (generalists, Solanaceae specialist, and Cucurbitaceae specialists). After the arrival of B. zonata, no change in the host range of specialist species was observed. However, the host ranges of two generalist species, Ceratitis quilicii and Ceratitis capitata, tended to shrink, as shown by the decreases in species richness and host plant α‐diversity. Our study shows increased host specialization by generalist phytophagous insects in the field following the arrival of an invasive species sharing part of their resources. These findings could be used to improve predictions of new interactions between invaders and recipient communities.